2007
DOI: 10.1063/1.2736654
|View full text |Cite
|
Sign up to set email alerts
|

The nature of nitrogen related point defects in common forms of InN

Abstract: A thermodynamic analysis of native point defect and dopant solubilities in zinc-blende III-V semiconductors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 36 publications
2
28
1
Order By: Relevance
“…This is indicative of a transition towards material with generally poorer crystal quality with a larger degree of mosaic tilts/twists and with increasing amounts of lattice distortions [36]. Hydrostatic stress observed in III-nitride semiconductors has been attributed to the existence of point defects, such as interstitials, vacancies, anti-site occupation, and substitutions in the film, as reported in previous literature [45][46][47][48]. Indium-rich nitride alloys have previously been shown to be very sensitive to inclusion of point and structural defects [49].…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…This is indicative of a transition towards material with generally poorer crystal quality with a larger degree of mosaic tilts/twists and with increasing amounts of lattice distortions [36]. Hydrostatic stress observed in III-nitride semiconductors has been attributed to the existence of point defects, such as interstitials, vacancies, anti-site occupation, and substitutions in the film, as reported in previous literature [45][46][47][48]. Indium-rich nitride alloys have previously been shown to be very sensitive to inclusion of point and structural defects [49].…”
Section: Resultsmentioning
confidence: 52%
“…Among point defects, the interstitials and anti-sites of indium at nitrogen positions can result in hydrostatic stress in the films. It has been shown that the interstitial nitrogen is dominant among those point defects in sputtered InN films [45,46]. In addition, the substitutions can contribute to structural defects when the elemental content of ternary alloys is within the miscibility gap.…”
Section: Resultsmentioning
confidence: 99%
“…of In-O. 19,20 The high-energy shoulder, peak 'ii', corresponds to OH groups -indicating significant amounts of dissociated H 2 O.…”
mentioning
confidence: 99%
“…Nitrogen vacancies, V N , associated with dislocations, 3,4 unintentional impurities, such as H ͑Refs. 2 and 5-9͒ and O, 6,8 and complexes of In vacancies with N on the In-site 10 have been suggested as possible sources for the unintentional n-type doping in InN.…”
mentioning
confidence: 99%